Cross-infection risk related to use of portable fans in a healthcare setting - Hylton, Chloe; Brown, Kerryanne; Mortimer, Kalani (International Journal of Infection Control, 2026)
Hospital environments pose infection risks. During a meticillin resistant Staphylococcus aureus (MRSA) outbreak in an adult Intensive Care Unit (ICU), a visibly contaminated bladeless Dyson® fan at the bedside of a previous outbreak patient prompted a microbiological investigation. Four sections of the bladeless Dyson® fan were swabbed to identify potentially pathogenic organisms, with confirmed isolates undergoing whole genome sequencing. Results identified MRSA, vancomycin resistant Enterococcus (VRE) and Aspergillus niger. The MRSA strain identified on the bladeless fan matched the outbreak strain. Existing research acknowledges the infection risks associated with inadequate ventilation and the use of fans in healthcare settings. The pandemic highlighted the importance of ventilation; however, comprehensive guidance on the use of portable fans in healthcare settings is yet to be provided. The contaminated fan was removed and disposed of, and trust wide communication was given recommending all portable fans to be removed from the trust. This case study confirmed the presence of potential pathogens on a bladeless Dyson® fan in an ICU. This further highlights the need for cleanable fan designs and research into the safe use of these devices to mitigate infection risks whilst addressing ventilation and cooling needs in healthcare settings.